The association between fetal fibronectin and spontaneous preterm birth in twin pregnancies with a shortened cervical length*. (2nd October 2018) - Matthews, Kathy C.; Gupta, Simi; Lam-Rachlin, Jennifer; Saltzman, Daniel H.; Rebarber, Andrei; Fox, Nathan S.
Abstract: Objective: To estimate the association between a positive fetal fibronectin (fFN) and spontaneous preterm birth (SPTB) in twin pregnancies with a shortened cervical length (CL). Study design: Retrospective cohort study of asymptomatic twin pregnancies managed by a single MFM practice from 2005 to 2016. We included all women with a shortened CL ≤25 mm at 22–28 weeks, and compared outcomes between women with a positive and negative fFN result. Results: One hundred fifty-five patients were included, 129 (83.2%) of whom had a negative fFN and 26 (16.8%) of whom had a positive fFN. Baseline characteristics were similar between groups, except for the CL at the time of diagnosis of short cervix (15 mm in the positive fFN group versus 20 mm in the negative fFN group, p = .002). The risk of SPTB <32 weeks was significantly higher in the positive fFN group (46.2 versus 12.6%, aOR 3.54, 95% CI 1.26, 9.92) and the mean gestational age at delivery was significantly earlier (31.1 versus 35.2 weeks, p < .001). Conclusions: In asymptomatic women with twin pregnancies and a shortened CL, a positive fFN is significantly associated with SPTB and can modify the risk substantially. If performing a screening CL assessment in a twin pregnancy, fFN testing should be done concurrently.